POLA INSERSI PARTENOKARPI, DEFH9-IAAM PADA GALUR TOMAT TRANSGENIK - Pardal, S.J.; Slamet, Slamet; Purnamaningsih, R.; Lestari, E.G. (BERITA BIOLOGI, 2014)
The development of seedless tomato fruits will be more attractive to consumers and industry. Artificial parthenocarpy can be induced through genetic crossing, hormone application or genetic engineering. Development of parthenocarpic tomatos has been done by inserting parthenocarpy gene, DefH9-iaaM into tomato genome via Agrobacterium tumefaciens. Sixty putative transgenic tomato lines were produced, and three events (lines) have been selected as the best event, i.e. OvR1#14-4, OvM2#10-1, OvM2#6-2. These lines contained the DefH9-iaaM based on PCR test. This research aimed was to determine the insertion patern of DefH9-iaaM gene in the progeny of transgenic tomatos lines. Parent variety Oval and line Cl 6046 were used as control plants. Results indicated that tomatos line OvR1#14-4 was still contained the inserted DefH9-iaaM gene and followed the Mendelian pattern (3:1) based on molecular analyses and Chi-square test results, while the others were not identified. Line OvR1#14-4 was required to be further evaluated for phenotypic and genotypic analyses for the expression of their parthenocarpy.